2021
DOI: 10.1002/anie.202105857
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic System‐Controlled Divergent Reaction Strategies for the Construction of Diversified Spiropyrazolone Skeletons from Pyrazolidinones and Diazopyrazolones

Abstract: A catalytic system‐controlled divergent reaction strategy was here reported to construct four types of intriguing spiroheterocyclic skeletons from simple and readily available starting materials via a precise chemical bond activation/[n+1] annulation cascade. The tetraazaspiroheterocyclic and trizazspiroheterocyclic scaffolds could be independently constructed by a selective N−N bond activation/[n+1] annulation cascade, a C(sp2)‐H activation/[4+1] annulation and a novel tandem C(sp2)‐H/C(sp3)−H bond activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 83 publications
0
20
0
Order By: Relevance
“…Likewise,the optimal reaction conditions for 4aaand 5aa were also separately explored (see Support Information for details) and the results displayed that when using [Cp*RhCl 2 ] 2 (4.0 mol %), Na 2 CO 3 (1 equiv) in MeCN/H 2 O( 4/1) at 60 8 8C for 4hunder Air atmosphere (condition B) and [Cp*RhCl 2 ] 2 (4.0 mol %), AgOAc (2 equiv), citric acid (2 equiv), 4 MS (100 mg) in MeCN at 80 8 8Cf or 4h under Ar atmosphere (condition C) as their respective catalytic systems,t he products 4aa and 5aa could be effectively prepared with 79 %a nd 81 %, respectively.T heir structures were unambiguously confirmed by their 1 Ha nd 13 CNMR spectra, mass spectrometry,and X-ray crystallographic analyses. [16] With the optimized reaction conditions identified, we firstly investigated the scope of pyrazolidinones 1 and coupling partners 2 under the optimal reaction condition (condition A) to build these novel tetraazaspiro[4.5]dec-3-enes 3 via as elective N À Nb ond activation and [5+ +1] annulation route (Scheme 2). Generally,t his transformation was compatible with all referred substrates.B esides 3aa could be obtained with an excellent 90 %yield, whether we introduced halogen atoms (F,C la nd Br), electron-withdrawing groups (CF 3 ,CN) or electron-donating groups (CH 3 and OCH 3 )into 4-position of benzene ring of substrates 1,t he reaction efficiencies were still maintained at an excellent level (Scheme 2, 3ba-3ha).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Likewise,the optimal reaction conditions for 4aaand 5aa were also separately explored (see Support Information for details) and the results displayed that when using [Cp*RhCl 2 ] 2 (4.0 mol %), Na 2 CO 3 (1 equiv) in MeCN/H 2 O( 4/1) at 60 8 8C for 4hunder Air atmosphere (condition B) and [Cp*RhCl 2 ] 2 (4.0 mol %), AgOAc (2 equiv), citric acid (2 equiv), 4 MS (100 mg) in MeCN at 80 8 8Cf or 4h under Ar atmosphere (condition C) as their respective catalytic systems,t he products 4aa and 5aa could be effectively prepared with 79 %a nd 81 %, respectively.T heir structures were unambiguously confirmed by their 1 Ha nd 13 CNMR spectra, mass spectrometry,and X-ray crystallographic analyses. [16] With the optimized reaction conditions identified, we firstly investigated the scope of pyrazolidinones 1 and coupling partners 2 under the optimal reaction condition (condition A) to build these novel tetraazaspiro[4.5]dec-3-enes 3 via as elective N À Nb ond activation and [5+ +1] annulation route (Scheme 2). Generally,t his transformation was compatible with all referred substrates.B esides 3aa could be obtained with an excellent 90 %yield, whether we introduced halogen atoms (F,C la nd Br), electron-withdrawing groups (CF 3 ,CN) or electron-donating groups (CH 3 and OCH 3 )into 4-position of benzene ring of substrates 1,t he reaction efficiencies were still maintained at an excellent level (Scheme 2, 3ba-3ha).…”
Section: Resultsmentioning
confidence: 99%
“…Chemie Forschungsartikel 21500 www.angewandte.de mainly involved the production of 4aa,b ut had almost nothing to do with the production of 5aa.Additively,treating 1o and 2a under condition Co nly produced 6oa [16] in 53 % yield rather than the target spiro-heterocyclic product, which indicated the gem-dimethyl effect was critical to the formation of 5 (Scheme 6e). Tw ocontrol experiments showed that the pyrazolidinone 1a could be oxidized to iminium intermediate 1a' ',which was akey intermediate for the formation of product 5aa under the reaction condition C( Scheme 6j).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inspired by these elegant pioneering studies and continuing our interest on the functionalization of inert chemical bonds, 5,6 in this work we endeavored to design and explore the reactions of N -phenoxyacetamides with diazopyrazolones 7 and diazooxindoles 8 with the aim of obtaining new chemical entities that have potential pharmaceutical and material applications. Serendipitously, we found two unprecedented distinct reaction modes of N -phenoxyacetamides under the catalysis of Rh( iii ).…”
Section: Introductionmentioning
confidence: 99%